Kedudukan Advokat Sebagai Penegak Hukum Dalam Hubungan Dengan Aparat Penegak Hukum Lainnya Untuk Menegakkan Hukum dan Keadilan - Dezonda R. Pattipawae (SASI, 2012)
With the enactment of Law Advocate gave an Advocate for proceeds in this country, becausethe existence of the Advocate has been recognized as one of the law enforcement officers whohad not been enacted or not the enforcement of Law Advocates. Role of Advocates as otherlaw enforcement officers are always considered Advocate at the time as an integral part thatdoes not have a strategic position in the system of law in Indonesia. Position advocate for lawenforcement officers to be not a figment, it is proved by the enactment of Law No. 18 Year2003 on Advocates. In Article 5, paragraph (1) expressly says that "Advocates status as lawenforcement, free and independent and guaranteed by laws and regulations. Pursuant toArticle 5 paragraph (1) of Law Advocates, the advocate should position is equal or equivalentother law enforcement officers (police, prosecutors and judges), but the reality of lawenforcement in Indonesia Advocates have not been treated or respected by other lawenforcement officials as law enforcement officers. This can be evidenced by the presence ofthe Advocate inspected, prosecuted and even convicted for their profession, but in theAdvocates Act clearly and explicitly set the immunities under Article 16 of Law No. 18 Year2003 on Advocate: "Advocates can't prosecuted both civil and criminal in carrying tugsprofession in good faith under on the interests of the defense of clients in court"